Disparate but not antagonistic: Classes of labour in cotton production in Burkina Faso - Bettina Engels (Journal of Agrarian Change, 2022)
This paper examines the variety of agrarian classes of labour and the challenges they face in organizing and pursuing their interests. By taking the cotton sector in Burkina Faso as a case study, it analyses how various `classes of labour' organize and mobilize for collective action to raise their claims: poor cotton farmers and workers in the cotton factories. Poor and middle farmers recently came to the fore when they boycotted cotton production in large numbers. The study focusses on the boycott campaign, and more broadly on class struggle and collective action by farmers and workers, on interclass alliances, and on capital's attempts to play the classes of labour against one another. The boycott campaign provides an outstanding case to analyse the interests of the various classes of labour and of opportunities for rural–urban mobilization and alliances across classes of labour. I argue that poor farmers and factory workers along the chain of cotton production can be considered as various classes of labour that are not necessarily antagonistic to one another but, first and foremost, to capital. In order to achieve radical transformation in the agrarian context, what is needed are networks and organizations to establish interclass solidarity and alliances.
Keywords: 630; Africa; Burkina Faso; class analysis; class struggle; classes of labour; cotton